In vivo rectal dosimeter with MRI marker - Euntaek Yoon; Jin Dong Cho; Chang Heon Choi; Jin Ho Kim; Jeong Ho Kim; Jong Min Park; Jung-in Kim (PLoS ONE, 2026)
Background Hypofractionated external beam radiotherapy for prostate cancer necessitates precise rectal dose evaluation. We fabricated a radiochromic polyurethane-based in vivo rectal dosimeter with a custom MRI marker and a patient-specific applicator for in vivo dose verification (IDV) during gated MR-image guided radiotherapy (MR-IGRT). Methods The dosimeter featured a radiochromic polyurethane active layer, incorporating leucomalachite green (LMG) and tartrazine. To accommodate anatomical variations, a detachable PMMA applicator was designed in five sizes. For localization, four elastomeric materials, including two polyurethane-based and two silicone-based materials, were evaluated as candidate MRI markers. Post-irradiation fading was assessed over time to evaluate measurement stability. A dose-response calibration was performed to establish a linear relationship between net optical density (OD) and absorbed dose. Furthermore, dose uncertainty was analyzed based on the law of error propagation. For verification, in vivo measurements were conducted for two patients and compared with TPS-calculated doses. Results Vyta Flex 20 was selected as the optimal MRI marker due to its high signal intensity and ease of fabrication. Post-irradiation net OD showed a dose-dependent temporal response, and the readout time was standardized to 2 h. The dosimeter’s sensitivity was 0.00253 cGy -1 . Dose uncertainties were determined to be 2.1%, 2.0%, and 1.6% at 100, 200, and 300 cGy, respectively. In vivo verification showed mean dose differences of 3.7 ± 1.4% (95% CI, 0.1–7.3%) for patient #1 and 5.9 ± 2.1% (95% CI, 0.8–11.1%) for patient #2. Measured doses were consistently higher than TPS-calculated doses, suggesting possible contributions from localization uncertainty in high-dose-gradient regions and the material-dependent response of the radiochromic active layer. Conclusion The fabricated radiochromic dosimeter with a custom MRI marker and adjustable applicator demonstrated preliminary feasibility as a proof-of-concept system for in vivo rectal dose verification during MR-IGRT. Further studies with larger patient cohorts and more treatment fractions are required to validate its reproducibility, statistical robustness, and clinical utility. Further refinement in positioning is also needed, particularly in dose-gradient regions.